Food Preferences of Seladang (Bos gaurus hubbackki) in Ulu Lepar, Pahang, Peninsular Malaysia - Yusof, Ebil (2009)
Seladang food preferences primarily depended on the habitat types within their home range. Shrubs and grasses were their main food sources. The types of food species preferred by seladang in each habitat types were unknown. In this study, the food species were identified and classified according to the intensity of browsing and grazing capacity of seladang within each habitat type such as in the primary forests, secondary forests and agricultural areas. Study plots and sub-plots were selected based on feeding habit and footprint signs. The results of this study found that 17 species of shrubs and 6 species of grasses were preferred by seladang. S. acuminata (7.95%) was the most preferable species of shrubs in the primary forest, Melastoma malabathricum (10.42%) in the secondary forest and Erythrina variegata(18.56%) in the agriculture area. The amount of grass species eaten by seladang is not significantly different but Imperata cylindrica was grazed in the primary forest compared to Paspalum conjugatum in the secondary forest and Paspalum vaginatum in agricultural area.